MAPPING GLOBAL RISKS FOR THE NEXT FIVE YEARS (2026–2030): AN INTEGRATED VUCA–PESTEL FRAMEWORK FOR CROSS-INDUSTRY STRATEGIC RESILIENCE - Johanes Kuntjoro Adisardjono (JURNAL ILMIAH EDUNOMIKA, 2026)
Global economic and organizational environments are increasingly shaped by heightened uncertainty arising from overlapping crises, rapid technological change, geopolitical fragmentation, and intensifying climate impacts. While prior studies have examined specific risks or sectoral contexts, comprehensive cross-industry risk mapping with a medium-term horizon remains limited. This study aims to identify and interpret dominant global risks for the period 2026–2030 using an integrated VUCA–PESTEL framework. The study adopts a conceptual–analytical research design, employing expert-informed risk synthesis based on authoritative global reports and selected academic literature. The analysis follows three stages: thematic risk identification, risk clustering, and multidimensional mapping, in which VUCA is treated as the operating environment and PESTEL as macro-environmental risk domains.The analysis identifies ten dominant global risk clusters with systemic and cross-industry implications, including climate-related systemic risk, food insecurity, geopolitical fragmentation, economic slowdown, technological disruption, cybersecurity vulnerability, erosion of public trust, regulatory acceleration, supply chain and energy insecurity, and reputational risk. The findings indicate that contemporary risks are increasingly interconnected and non-linear, challenging traditional silo-based risk management approaches. This study extends existing approaches by integrating VUCA and PESTEL into a unified framework for medium-term global risk mapping, supporting anticipatory risk governance and organizational resilience across industries. Keywords: Global Risk; VUCA - PESTEL; Risk Governance; Strategic Foresight; Organizational Resilience